A unifying convex analysis and switching system approach to consensus with undirected communication graphs - Goebel, Rafal; Sanfelice, Ricardo G. (Automatica (Oxford), 2020)
Switching between finitely many continuous-time autonomous steepest descent dynamics for convex functions is considered. Convergence of complete solutions to common minimizers of the convex functions, if such minimizers exist, is shown. The convex functions need not be smooth and the dynamics may be subject to constraints. Since the common minimizers may represent consensus in a multi-agent system modeled by an undirected communication graph, several known results about asymptotic consensus are deduced as special cases. Extension to a time-varying case is included.